(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This paper examines the role of Material Flow Cost Accounting (MFCA) in enhancing innovation for environmental sustainability, specifically in the context of refining companies. The study focuses on the implementation of MFCA as a technique for reducing carbon dioxide emissions and material losses, with an emphasis on both the economic and environmental impacts. The research sample comprises three refining companies (names withheld due to confidentiality), and the aim is to assess whether MFCA can contribute to material loss reduction and improve sustainability practices.SPSS software was employed for statistical analysis to test the research hypotheses. The findings suggest that combining MFCA with environmental sustainability initiatives can serve as a strategic tool for companies to address logistical challenges, reduce environmental harm, and improve competitiveness. By adopting MFCA, companies can not only reduce their carbon footprint but also develop environmentally friendly products, gaining a competitive edge in the global market.Key results indicate that MFCA provides valuable insights into both physical and financial aspects of production, highlighting areas of material waste, CO2 emissions, and non-commodity output. By focusing on material productivity improvements and waste reduction, MFCA enables companies to decrease environmental harm, enhance operational efficiency, and make data-driven decisions that promote long-term sustainability.